Nonlinear Analysis and Optimization with Applications - Du, Wei-Shih; Chu, Liang-Ju; He, Fei; Precup, Radu (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Nonlinear analysis has wide and significant applications in many areas of mathematics, including functional analysis, variational analysis, nonlinear optimization, convex analysis, nonlinear ordinary and partial differential equations, dynamical system theory, mathematical economics, game theory, signal processing, control theory, data mining, and so forth. Optimization problems have been intensively investigated, and various feasible methods in analyzing convergence of algorithms have been developed over the last half century. In this Special Issue, we will focus on the connection between nonlinear analysis and optimization as well as their applications to integrate basic science into the real world.